Bivariate Assessments of Real Exchange Rates Using PPP Data - Zalduendo, Juan. (Washington, D.C. : International Monetary Fund, 2008)
This paper focuses on assessments of real exchange rates using PPP data and examines their limitations when these are based exclusively on bivariate estimations. It begins by presenting an analytical framework of the real exchange rate that shows that these estimations make many restrictive assumptions. In turn, the empirical evidence presented shows that the estimates are not robust to changes in sample, such as those that arise from differences in incomes per capita. The conclusion is that the bivariate assessment of real exchange rates do not control for the heterogeneity that exists across countries, thus limiting their usefulness. This critique of bivariate estimations does not apply however to multivariate approaches such as utilized by CGER.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet